Some Challenges and Opportunities of QOS over Wireless Sensor Networks: A Review: Exploring the Requirements, Challenges, and Opportunities of QoS Management in Wireless Sensor-Actuator Networks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A wireless sensoractuator network (WSAN) is a group of sensors and actuators that are geologically distributed and interconnected by wireless networks. Sensors assemble information about the condition of actual world. Actuators respond to this information by performing suitable activities. WSANs subsequently empower cyber systems to screen and control the conduct of the actual world. WSANs are developing at an enormous movement, much the same as the detonating advancement of Internet. Supporting quality of service (QoS) will be of basic significance for pervasive WSANs that fill in as the network infrastructure of assorted applications. To start new research and improvement interests in this field, this paper looks at and examines the necessities, basic challenges, and open research issues on QoS the executives in WSANs.